Q. 235.0( 1 Vote )

In the e

Answer :

We have,

(1 + a)m+n = [m+nC0 + m+nC1a1 + m+nC2a2+…… m+nCr

ar + …… + m+nCm+n am+n

Coefficient of am = m+nCm =

Also the coefficient of an

= m+nCn =

Clearly, m+nCm = m+nCn

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses